The Economic Performance of Central Europe Metropolises. A Comparative Approach - Arkadiusz Mroczek (Comparative Economic Research. Central and Eastern Europe, 2021)
Since the fall of communism, the big cities of Central Europe have been included in the international metropolitan network, and their economic performance has improved significantly. Based on that, it can be asserted that the whole region is undergoing a process of metropolisation, which may be manifested by a focus of development in the limited areas of metropolises. Therefore this paper aims to present the results of a closer examination of this process in Central Europe. It is based on a comparative analysis of the metropolises in relation to their countries in terms of economic performance. A taxonomic approach based on Hellwig's development pattern is adopted. The available Eurostat data (NUTS 3 level) on a range of socio-economic characteristics is used. The study results show that the economic performance of Central European metropolises is relatively closer to Western Europe's cities than the countries' non-metropolitan parts. Highlighting development issues in Central Europe from the spatial-metropolitan point of view is the paper's added value.
Keywords: F60; O18; R19; 330; metropolises; Central Europe; metropolisation; taxonomy